2020
DOI: 10.1161/atvbaha.120.314143
|View full text |Cite
|
Sign up to set email alerts
|

A Role for MMP-10 (Matrix Metalloproteinase-10) in Calcific Aortic Valve Stenosis

Abstract: Objective: Aortic valve (AV) calcification plays an important role in the progression of aortic stenosis (AS). MMP-10 (matrix metalloproteinase-10 or stromelysin-2) is involved in vascular calcification in atherosclerosis. We hypothesize that MMP-10 may play a pathophysiological role in calcific AS. Approach and Results: Blood samples (n=112 AS and n=349 controls) and AVs (n=88) from patients undergoing valve replacement were analyzed. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
2
34
0
2
Order By: Relevance
“…Data from in vitro studies have demonstrated that inhibition of NF‐κB prevents up‐regulation of MMP1, MMP3 and MMP9 production from fibroblasts and vascular smooth muscle cells 77 . The valvular expression of several MMPs has been shown within aortic stenotic valves 78,79 . An in vitro study by Matilla et al 79 revealed that MMP‐10 in VIC cultures increased expression of inflammatory (IL‐1β), fibrotic (α‐smooth muscle actin, vimentin, collagen) and osteogenic (BMP‐4, BMP‐9, osteopontin, Sox9 and Smad1/5/8) markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from in vitro studies have demonstrated that inhibition of NF‐κB prevents up‐regulation of MMP1, MMP3 and MMP9 production from fibroblasts and vascular smooth muscle cells 77 . The valvular expression of several MMPs has been shown within aortic stenotic valves 78,79 . An in vitro study by Matilla et al 79 revealed that MMP‐10 in VIC cultures increased expression of inflammatory (IL‐1β), fibrotic (α‐smooth muscle actin, vimentin, collagen) and osteogenic (BMP‐4, BMP‐9, osteopontin, Sox9 and Smad1/5/8) markers.…”
Section: Resultsmentioning
confidence: 99%
“…The valvular expression of several MMPs has been shown within aortic stenotic valves 78,79 . An in vitro study by Matilla et al 79 revealed that MMP‐10 in VIC cultures increased expression of inflammatory (IL‐1β), fibrotic (α‐smooth muscle actin, vimentin, collagen) and osteogenic (BMP‐4, BMP‐9, osteopontin, Sox9 and Smad1/5/8) markers. The addition of a physiological MMP inhibitor (the tissue inhibitor of metalloproteinases type 1) to cultured human VICs prevented the release of pro‐inflammatory and osteogenic factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, among the genes selectively upregulated in Gata4KD , Il11 is a key mediator of organ fibrosis, possible downstream effector of TGF β [39]. Among genes upregulated in Tbx20KD, Heyl , downstream effector of Notch, is involved in cardiogenesis and is thought to repress Gata4 expression [40], Mmp10 is upregulated in patients with end-stage HF [41], and it is involved in valve ossification [42]. KEGG pathway analyses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OPN is also a pivotal intrinsic factor for regulating cartilage degradation due to its effects on the expression of MMP-13 and proteoglycan loss [ 9 ]. Several MMPs have been reported to regulate OPN expression; for example, MMP-9 can cleave an OPN fragment to mediate tumor immune escape, while the MMP-10 can induce the overexpression of OPN in calcific aortic valve stenosis [ 10 , 11 ]. The elevated expression of OPN, which was found in the joints of OA, is deemed to be correlated with the severity of joint lesions in OA [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%